STRATEGI KOMUNIKASI DALAM PENYALURAN BANTUAN LANGSUNG TUNAI (BLT) - Jayus Jayus; Infa Wilinday; Nolly Medya Putra (Universitas Pahlawan Tuanku Tambusai, 2022)
Covid-19 is still a very big concern for the Indonesian people and there are many losses caused by this pandemic. The government makes policies in dealing with the Covid-19 pandemic, with the enactment of the PSBB as stated in Government Regulation No. 21 of 2020. This virus has a huge impact on the economy because it reduces people's income, whether it's the poor or those who can afford it. Since the COVID-19 pandemic, people have been asked to obey government rules, namely to keep their distance and stay at home, which makes it difficult for people to stay healthy. communicate verbally. To overcome the decline in people's income due to Covid-19, the Indonesian government issued a policy by providing assistance in the form of money or often known as Direct Cash Assistance (BLT). It can be concluded that the distribution of Village Fund BLT is on time and follows the existing mechanism. Meanwhile, in terms of the accuracy of making choices, it can be concluded that the village government has worked according to the procedure. This is based on the statements of the people who directly felt the impact of BLT and were direct actors in the field. Keywords: BLT, Covid-19 Virus, Social Distancing